2016
DOI: 10.1186/s12962-016-0060-5
|View full text |Cite
|
Sign up to set email alerts
|

What are we paying for? A cost-effectiveness analysis of patented denosumab and generic alendronate for postmenopausal osteoporotic women in Australia

Abstract: ObjectiveZoledronic acid and denosumab were funded by the Australian government for the management of osteoporosis at an equivalent price to alendronate. The price of alendronate has declined by around 65 %, but the price of the other two therapies has remained stable. Using data published since the listing, this paper reports current estimates of the value of denosumab compared to alendronate from an Australian health system perspective.MethodsA cohort-based state transition model was developed that predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
1
18
1
1
Order By: Relevance
“…However, we found that some studies including both direct and indirect costs were not defined as having a societal perspective, although this was the original information stated by authors reported in Table 1; no adjustment and correction were made for this. Nineteen studies applied a lifetime horizon while others considered truncated time horizons [10][11][12][13][14][15]. A Markov model was used in 21 studies, consisting of a Markov cohort model (n = 12) or a Markov microsimulation model (n = 9).…”
Section: Idenɵficaɵonmentioning
confidence: 99%
“…However, we found that some studies including both direct and indirect costs were not defined as having a societal perspective, although this was the original information stated by authors reported in Table 1; no adjustment and correction were made for this. Nineteen studies applied a lifetime horizon while others considered truncated time horizons [10][11][12][13][14][15]. A Markov model was used in 21 studies, consisting of a Markov cohort model (n = 12) or a Markov microsimulation model (n = 9).…”
Section: Idenɵficaɵonmentioning
confidence: 99%
“…50,51 Five manufacturer-sponsored studies were identified and two independent studies—one comparing denosumab and alendronate and another comparing anabolic drugs (abaloparatide and teriparatide) to no therapy. 41,4548,52,53…”
Section: Discussionmentioning
confidence: 99%
“…31,34 Up to 60% of studies examined a long time horizon of a lifetime (n = 9), whereas 2 studies utilized a 5-year horizon 32,35 and 4 studies assessed the impact over a 10-year time horizon. 31,34,36,37 Among 11 articles that reported discounting in the methods, the majority (55%) discounted both cost and outcomes by 3%, whereas other studies utilized discounts of 1.5%, 41 3.5%, 34 and 5%. 32,36,38 The annual cost (2017 US dollars) of denosumab ranged from $420.81 in Australia 36 to $1761.62 in the United States, 14 which was always higher than the cost of generic alendronate, which ranged from $25.11 in Sweden 33 to $400.44 in Canada.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…31,34,36,37 Among 11 articles that reported discounting in the methods, the majority (55%) discounted both cost and outcomes by 3%, whereas other studies utilized discounts of 1.5%, 41 3.5%, 34 and 5%. 32,36,38 The annual cost (2017 US dollars) of denosumab ranged from $420.81 in Australia 36 to $1761.62 in the United States, 14 which was always higher than the cost of generic alendronate, which ranged from $25.11 in Sweden 33 to $400.44 in Canada. 38 Only 2 studies reported having no conflicts of interest, 39,42 whereas 7 studies included industry authors.…”
Section: Cost-effectivenessmentioning
confidence: 99%